1989
DOI: 10.1016/0167-2789(89)90060-2
|View full text |Cite
|
Sign up to set email alerts
|

Slow time-periodic solutions of the Ginzburg-Landau equation

Abstract: In this paper we study the behaviour of solutions of the form if(z, t) = q~(z) e-i~wt (e << 1) of the rescaled Ginzburg-Landau equation, ~k, = [1-(1 + iB)l~kl2]~k + (1 + iA)~kzz, for A = ca, B = eb, w plays the role of free parameter. This leads to a perturbation analysis on a complex Duffing equation (similar to the analysis of Holmes [Physica D 23 (1986) 84]). We show that the spatial quasiperiodic solutions (of the unperturbed, e = 0, case) disappear due to the perturbation and prove the existence of degen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 14 publications
3
52
0
1
Order By: Relevance
“…(The Poincar6 map has no fixed points for parameter combinations outside this region.) This region, F, does not depend on the coefficients c~ = ca and/3 = Eb of Equation We remark here that this result is a significant extension of the work done in [12]: in that paper it was shown that none of the quasi-periodic solutions of the integrable limit, except for a family of degenerate periodic solutions, survive the perturbation. However, in [12] we considered v = 0.…”
Section: U(x T) = Gt(x + Vt)e -Iw'supporting
confidence: 60%
See 3 more Smart Citations
“…(The Poincar6 map has no fixed points for parameter combinations outside this region.) This region, F, does not depend on the coefficients c~ = ca and/3 = Eb of Equation We remark here that this result is a significant extension of the work done in [12]: in that paper it was shown that none of the quasi-periodic solutions of the integrable limit, except for a family of degenerate periodic solutions, survive the perturbation. However, in [12] we considered v = 0.…”
Section: U(x T) = Gt(x + Vt)e -Iw'supporting
confidence: 60%
“…Furthermore, we discuss briefly the relation between this paper and earlier work on the weakly complex Ginzburg-Landau equation [12].…”
Section: U(x T) = Gt(x + Vt)e -Iw'mentioning
confidence: 99%
See 2 more Smart Citations
“…See Holmes [24], Sirovich and Newton [34], Landman [27], Bernoff [3], Doelman [11,12], Schopf and Kramer [31] and references therein, for example. Recently,…”
Section: Background and Definitionsmentioning
confidence: 99%